Detection of Volatile Organic Compound with an Ion Mobility Spectrometry Cell Type Device with a Corona Discharge Ionization Source - Boggio, Norberto Gabriel (2011)
Using the cross flow ion mobility spectrometry (CFIMS) concept, together with a pulsed corona discharge ionization source, a prototype of IMS cell type device was constructed and tested. In this work, we report the experimental conditions to set up the instrument and the analytical results based on the principal components analysis (PCA) obtained in the detection of toluene, acetone, ethanol and isoamyl acetate on gas phase. The advantages of this new design are the high ions concentration obtained compared to the commonly used 63Ni source, the simplicity of the CFIMS and the rapid response time.